Women need not apply: gendered institutional change in Antarctica and Outer Space. Issue 2 (3rd July 2017) - Seag, Morgan
Abstract: 1983 was a year of firsts for women in two of the world's leading institutions of scientific exploration: NASA sent a woman into space for the first time, and the British Antarctic Survey (BAS) sent women to Antarctica for the first time. But by 1986, while female astronauts had continued to launch into space, women remained barred from applying to nearly three-quarters of BAS's advertised positions. An author writing in The Geographical Magazine expressed frustration: "If women can go into space they can certainly do field work in Antarctica". The Director of BAS expressed a different sentiment: "No valid parallels can be made … with space flight". Using the overlapping histories of BAS and NASA as a starting point, this paper offers a way to think through the relational trajectories of Antarctica and Outer Space. It applies an institutionalist frame to hundreds of previously unexamined records in the BAS Archives as well as recent literature dealing with gender at NASA, demonstrating the value of this frame to shed new light on relational histories and gendered spatialities. This approach grounds our view of Antarctica and Outer Space in histories of gendered labour; it also contributes to growing critique of frontier exceptionality by illustrating the historical entanglement of Antarctica and Outer Space with broader processes of gendered change.